The acute effects of resistance exercise on affect, anxiety, and mood - practical implications for designing resistance training programs - Cavarretta, D. J.; Hall, E. E.; Bixby, W. R. (International Review of Sport and Exercise Psychology, 2019)
Research in aerobic exercise has linked the affective responses (pleasure-displeasure) experienced during exercise to future exercise participation. While this is yet to be confirmed in anaerobic activities, it can be inferred that making resistance exercise (RE) more psychologically rewarding is an important consideration. The purpose of this article is to review the acute effects of RE on affect, anxiety, and mood and to draw conclusions on how to maximize feelings of pleasure in an effort to increase rates of participation. This review provides evidence to support lower training volumes performed at low to moderate intensities (50-70% 1RM) with long inter-set rest intervals (90-150 s). Additional recommendations are provided based on physiological and theoretical support, but there is a strong need for more research on the affective experience of RE.